Buran, S. (Ed.). (2020). Edebiyatta posthümanizm. TPLondon. - Zampaki, Nikoleta (Journal of Posthumanism, 2022)
The edition entitled EdebiyattaÂ Posthümanizm [Posthumanism in Literature] is the first edition in the Turkish language which introduces the narrative of posthumanism in Anglo-American Literature and Culture. This edition is the first book of the Posthumanism Series by TPLondon, edited by Sümeyra Buran, that examines how posthumanism is conceptualized in literary writing by studying the western traditional binaries, e.g. human and nature, human and non-humans, and so forth, that have nurtured the ideology and mentality of western societies for centuries. This edition also examines the contribution of literature in presenting alternative ideas and thoughts by laying the ground of Posthumanities in Turkey by opening new doors for the readers to understand the changing status of man and the nature of the relationship (e.g. hybrid, parasitic, etc.) between the human and more-than-human world.